Study of quality of life in epilepsy patients with psychiatric co-morbidities using QOLIE-31 - Amruth, Gujjar; Srikanteswara, Praveen-kumar; Nataraju, Boraiah; Kasturi, Pandiyan (International Journal of Epilepsy, 2014)
Background Epilepsy is a neurological condition affecting both the sexes in all age groups and is associated with psychiatric co-morbid conditions. There is a paucity of available published data regarding psychiatric co-morbid conditions and quality of life in patients with Epilepsy (PWE) from developing countries.Methods We evaluated the quality of life in 80 PWE, 80 with asthma (asthma control subjects: AC) and 80 normal healthy patients (normal control subjects: NC) using the QOLIE-31 item inventory.Results Psychiatric co-morbid conditions are more common in PWE (32.50%) as compared to the AC (17.5%) and NC (7.5%). The quality of life in PWE was significantly lower when compared to control subjects and it was further low in the presence of co-morbid psychiatric disorders.Conclusion Co-morbid psychiatric disorders should be identified and documented in PWE and treating these disorders apart from the control of seizures may significantly improve their quality of life.
Keywords: Psychiatric co-morbidity; QOLIE; MINI; Epilepsy